A Comparison between Static and Repeated Load Test to Predict Asphalt Concrete Rut Depth - Alzaidy, F.; Albayati, A. H. K. (Engineering, Technology & Applied Science Research, 2021)
Rutting has a significant impact on the pavements' performance. Rutting depth is often used as a parameter to assess the quality of pavements. The Asphalt Institute (AI) design method prescribes a maximum allowable rutting depth of 13mm, whereas the AASHTO design method stipulates a critical serviceability index of 2.5 which is equivalent to an average rutting depth of 15mm. In this research, static and repeated compression tests were performed to evaluate the permanent strain based on (1) the relationship between mix properties (asphalt content and type), and (2) testing temperature. The results indicated that the accumulated plastic strain was higher during the repeated load test than that during the static load tests. Notably, temperature played a major role. The power-law model was used to describe the relationship between the accumulated permanent strain and the number of load repetitions. Furthermore, graphical analysis was performed using VESYS 5W to predict the rut depth for the asphalt concrete layer. The α and µ parameters affected the predicted rut depth significantly. The results show a substantial difference between the two tests, indicating that the repeated load test is more adequate, useful, and accurate when compared with the static load test for the evaluation of the rut depth.